2019
DOI: 10.1159/000500204
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Cardiotoxicity and Efficacy of Anthracycline-Based Therapies in Breast Cancer: A Network Meta-Analysis of Randomized Clinical Trials

Abstract: The effects of anthracycline-based chemical therapies on breast cancer are controversial and inconclusive. We undertook a network meta-analysis to assess the cardiotoxicity and effects of anthracycline therapies in breast cancer. The PubMed, Embase, and Cochrane databases up to August 2018 were reviewed. We identified 19 randomized clinical trials including 3,484 patients with breast cancer which assessed both cardiotoxicity and the effects of anthracycline-based therapies. Eligible studies included the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…Because of its protective effect on acute cardiotoxicity, dexrazoxane is currently widely applied in clinical practise. 91,104 -106 Dexrazoxane leads to reduction of cardiac injury, as reflected by Troponin T levels 107 and echocardiographic parameters. 108 A multicenter randomized phase III study found a significant reduction in cardiac events (39% vs 13%) and congestive HF (11% vs 1%) with dexrazoxane in high-risk patients previously treated with anthracyclines.…”
Section: Preventive Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its protective effect on acute cardiotoxicity, dexrazoxane is currently widely applied in clinical practise. 91,104 -106 Dexrazoxane leads to reduction of cardiac injury, as reflected by Troponin T levels 107 and echocardiographic parameters. 108 A multicenter randomized phase III study found a significant reduction in cardiac events (39% vs 13%) and congestive HF (11% vs 1%) with dexrazoxane in high-risk patients previously treated with anthracyclines.…”
Section: Preventive Strategiesmentioning
confidence: 99%
“…88 In contrast, studies on the cardiotoxicity profile of epirubicin are inconclusive. While some studies suggest reduced cardiotoxicity by epirubicin in comparison with doxorubicin, 90,91 others mention isoequivalent toxicity profiles of the 2 anthracycline agents. 88 Beside these conventional therapies, efforts have been made to reduce cardiotoxicity by modifying the chemical structure of anthracyclines.…”
Section: Choice Of Anthracycline Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, therapies other than anthracyclines should be considered when they are superior or equally effective (e.g., docetaxel/ cyclophosphamide) for cases of BC. [146][147][148] Use of doxorubicin liposomal. There is an alternative formulation of either encapsulated doxorubicin or liposomal (instead of doxorubicin or in patients who have already exceeded doses).…”
Section: • Adjusted Dose Maintain Cumulative Dosementioning
confidence: 99%
“…Addressing this knowledge gap is important, as numerous monotherapy and combination therapy regimens are often available to treat each patient. Here, we show that breast cancer cells resistant to either doxorubicin or epirubicin, two anthracycline drugs that are used interchangeably for breast cancer treatment ( Mao et al, 2019 ), rely on distinct primary metabolic processes, and that exploiting these dependencies may impair the growth of treatment resistant breast cancers.…”
Section: Introductionmentioning
confidence: 99%